Categorization of weathering stresses for photovoltaic modules. Issue 2 (6th April 2018) - Koehl, Michael; Heck, Markus; Wiesmeier, Stefan
Abstract: Solar energy conversion requires permanent outdoor operation of essential components such as photovoltaic modules, solar collectors, or reflectors. They are exposed to weathering stresses. The stress levels depend on the local climates. Monitoring of climatic properties and sample properties in different climatic zones (alpine, arid, maritime, moderate, and tropical) during several years provided the base for categorization of these climates. The local climate does not differ very much from year to year in terms of frequency distributions, but big differences are found for different regions or climatic zones. Especially, the solar irradiation is very location‐dependent. The alpine location shows the highest UV irradiation. The UV fraction of the solar irradiation is varying between 2.2% (tropics) and 4.7% (alps). The temperature histograms can be modeled by Gaussian distribution functions. The maritime histogram is very slim and high, showing the cooling by the sea and the wind. Several approaches for a categorization of these local climates can be applied: Mean temperatures, effective temperatures, or the corresponding constant testing time for fictive degradation processes with arbitrary activation energy. The categorization of the relative humidity revealed humid climates in the alpine and the tropical test site, when considering the time of wetness (rh > 80%). Obviously, the humidity stress or the corrosivity would be very different at those sites. Therefore, a more holistic approach considering more stress factors simultaneously would be more appropriate for the categorization. The interaction between the samples and the climate creates the so‐called micro‐climate which is the real stress on the samples, such as surface temperature, daily temperature cycles, surface humidity, or temperature‐enhanced photo‐degradation. The conditions for accelerated life testing (ALT) modeled on the base of monitored climatic data and sample temperatures are different for the different locations. They offer another possibility for categorization of the climatic stresses and the option for designing climate‐adapted components. Abstract : Solar energy systems are stressed by weathering. The quantitative load during the service lifetime depends on the local climate. The evaluation of time series of climatic data and their impact on the materials allow the assessment of the stress ranges for the development of accelerated life tests.